Cost of capital and earnings transparency - Barth, Mary E.; Konchitchki, Yaniv; Landsman, Wayne R. (Journal of Accounting and Economics, 2013)
We provide evidence that firms with more transparent earnings enjoy a lower cost of capital. We base our earnings transparency measure on the extent to which earnings and change in earnings covary contemporaneously with returns. We find a significant negative relation between our transparency measure and subsequent excess and portfolio mean returns, and expected cost of capital, even after controlling for previously documented determinants of cost of capital.